Optoelectronic switching of nanowire-based hybrid organic/oxide/semiconductor field-effect transistors - Baek, Eunhye; Pregl, Sebastian; Shaygan, Mehrdad; Roemhildt, Lotta; Weber, Walter M.; Mikolajick, Thomas; Ryndyk, Dmitry A.; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni) (Nano Research, 2015)
A novel photosensitive hybrid field-effect transistor (FET) which consists of a multiple-shell of organic porphyrin film/oxide/silicon nanowires is presented. Due to the oxide shell around the nanowires, photoswitching of the current in the hybrid nanodevices is guided by the electric field effect, induced by charge redistribution within the organic film. This principle is an alternative to a photoinduced electron injection, valid for devices relying on direct junctions between organic molecules and metals or semiconductors. The switching dynamics of the hybrid nanodevices upon violet light illumination is investigated and a strong dependence on the thickness of the porphyrin film wrapping the nanowires is found. Furthermore, the thickness of the organic films is found to be a crucial parameter also for the switching efficiency of the nanowire FET, represented by the ratio of currents under light illumination (ON) and in dark conditions (OFF). We suggest a simple model of porphyrin film charging to explain the optoelectronic behavior of nanowire FETs mediated by organic film/oxide/semiconductor junctions.
CRIS-Team Scopus Importer:2023-03-20
Keywords: hybrid nanoelectronics; optoelectronic switching; organic/oxide/semiconductor junctions; porphyrin; silicon nanowire field-effect transistors